Adherence of Lactobacillus salivarius to HeLa Cells Promotes Changes in the Expression of the Genes Involved in Biosynthesis of Their Ligands - Martín, Carla; Fernández-Vega, Iván; Suárez, Juan E.; Quirós, Luis M. (Frontiers in Immunology, 2020)
The attachment of a variety of lactobacilli to the mucosal surfaces is accomplished through the interaction of OppA, a superficial bacterial protein also involved in oligopeptide internalization, and the glycosaminoglycan moiety of the proteoglycans that form the epithelial cell glycocalyx. Upon the interaction of the vaginal isolate Lactobacillus salivarius Lv72 and HeLa cell cultures, the expression of oppA increased more than 50-fold over the following 30 min, with the overexpression enduring, albeit at a lower rate, for up to 24 h. Conversely, transcriptional analysis of 62 genes involved in proteoglycan biosynthesis revealed generalized repression of genes whose products catalyze different steps of the whole pathway. This led to decreases in the superficial concentration of heparan (60%) and chondroitin sulfate (40%), although the molecular masses of these glycosaminoglycans were higher than those of the control cultures. Despite this lowering in the concentration of the receptor, attachment of the lactobacilli proceeded, and completely overlaid the underlying HeLa cell culture.